Analysis of the Effects of Taste, Promotion and Service Quality on Customer Satisfaction at King Kuphi Ulee Kareng Medan - Icha Aulia Zahra; Nurafrina Siregar; Yossie Rossanty (Cattleya Darmaya Fortuna, 2026)
This study aims to determine and analyze the influence of taste, promotion, and service quality on customer satisfaction at King Kuphi Ulee Kareng Medan. This study uses a quantitative approach with descriptive and causal research types through a survey method. Data collection was conducted using a research instrument in the form of a questionnaire with a Likert scale. The population in this study consists of customers of King Kuphi Ulee Kareng Medan, with a sample size of 134 respondents. The data analysis techniques used include multiple linear regression analysis, validity tests, reliability tests, classical assumption tests, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²). The pre-survey results indicate that the taste variable falls into the good category, the promotion variable into the fairly good category, the service quality variable into the good category, and the customer satisfaction variable also into the good category. The results of this study suggest that taste, promotion, and service quality are presumed to have a positive and significant influence on customer satisfaction at King Kuphi Ulee Kareng Medan. This study has limitations because it was conducted only on customers of King Kuphi Ulee Kareng Medan with a limited number of respondents and focused only on the variables of taste, promotion, and service quality. It is hoped that this study can contribute to the development of marketing management science, particularly regarding customer satisfaction in the local culinary and café industries, and can serve as a basis for consideration by the management of King Kuphi Ulee Kareng in improving product quality, promotional strategies, and service quality for customers.